Bladder cancer in patients with neurogenic bladder disorder: a comparative study of different etiologies: topic paper - Mühlbauer, Julia; Klotz, David; Büttner, Sylvia; Stein, Raimund; Younsi, Nina (World journal of urology, 2022)
The objective of this study was to conduct a comparative study of different etiologies of neurogenic bladder disorders (NBDs) in patients with bladder cancer (BC) regarding patient- and tumor-related parameters and their oncological outcome.